Experimenting LoRa‐compliant solutions in Real‐World Scenarios. Issue 2 (17th December 2019) - Tresca, Giulia; Vista, Francesco; Boccadoro, Pietro
Abstract : Long Range (LoRa) is one of the most promising technologies in the context of Low Power Wide Area Networks (LPWANs). Thanks to its unique features, it addresses some of the most representative Internet of Things (IoT) constraints, since it lowers energy footprints over long‐distance communications. In the context of environmental monitoring, many LoRa‐compliant solutions are now available. This work proposes a case‐study analysis of rapid prototyping platforms that leverage both the simplicity and effectiveness of the LoRa technology in the context of outdoor communications. The conducted experimental campaign concretely demonstrated the effects of the Spreading Factor (SF), Bandwidth (BW), and Coding Rate (CR) on the communication range in urban environments. At the same time, results highlighted that, in a 7 km range, the Packet Loss Ratio (PLR) can be as low as 15%.